CURRENT PROBLEMS OF THE DIAGNOSTIC AND TREATMENT TACTICS OF PURULENT-INFLAMMATORY DISEASES AND SEPSIS - Остапюк, Л. Р.; Коваленко , О. М. (Українські медичні вісті, 2023)
CURRENT PROBLEMS OF THE DIAGNOSTIC AND TREATMENT TACTICS OF PURULENT-INFLAMMATORY DISEASES AND SEPSIS